Atretic aortic coarctation in a 32-year-old woman diagnosed after her third pregnancy, treated percutaneously using a covered stent - Al-Ammouri, Iyad (J Cardiol Cases, 2015)
Atretic aortic coarctation is a severe form of coarctation of aorta, where there is loss of luminal communication at the site of aortic isthmus. We present a case of a 32-year-old woman who had long-standing, treatment-resistant hypertension. She had three pregnancies. The third pregnancy ended in premature labor of a newborn female infant who was found to have severe coarctation of aorta. This diagnosis in the newborn child prompted proper evaluation of the mother, who was found to have atretic coarctation. The woman was treated successfully using a covered Advanta V12 stent (Atrium, Hudson, NH, USA), after percutaneous needle puncture of the atretic isthmus. Anatomical orientation of the aorta at the site of coarctation and its relationship to the safety of needle puncture approach are discussed. This case brings an old lesson to the table, where proper evaluation of severe, treatment-resistant hypertension in adults should include screening for secondary causes. <Learning objective: Evaluation of severe and resistant systemic hypertension in adults should include screening for aortic coarctation. Pregnancy in women with coarctation of aorta carries significant risk to both the woman and the fetus. Atretic coarctation is a severe form of coarctation where there is complete obstruction of aortic isthmus. This can be treated successfully by percutaneous approach using covered stents.>